К морфологии преимагинальных стадий некоторых видов слепней (Diptera, Tabanidae) юга Украины - Долин, В.Г.; Андреева, Р.В. (Вестник зоологии, 1981)
Previously unknown larvae and pupae o f Chrysops italicus Mg., Tabanus smirnovi O 1 s. and Hybomitra ukrainica O 1 s. distributed in the south-western Black Sea territory and in the Crimea are described. Data on ecology ot these species are given.